Meningkatkan Wisata Bersepeda Bagi Wisatawan yang Ramah Difabel di Desa Kembang Kabupaten Kulon Progo - Dharomesz, Vonezyo Yupanzara (Lembaga Penelitian dan Pengabdian pada Masyarakat, 2022)
The Student Study Service (KKN) or KKN 80 is carried out from October to November 2021 by the society 5.0 method or without field diving. Development of KKN launch 80 kto l and kulon progo districts, yogyakarta province. The 116 Unit x group is in Kembang Village, Nanggulan district, Kulon Progo, Yogyakarta. The purpose of KKN activity is to be a forum for students to work, provide an explanation of the village’s potential, then provide knowledge about what are the benefits of bicycle tourism for the surrounding community, increase empathy and concern for the surroundings, realizing a sense of responsibility and solidarity, and foster a disciplined attitude in working together. The program run by the 116 group is known as village power and pocketbook. Among the emissions to be produced are (1) ebook and videos development of potential village blossoms for cycling; (2) ebook and the friendly development videos for those with disabilities. Each group member also works on an individual program entitled tourism, science, and entrepreneurship.